TERRITORIAL ANALYSIS, DEVELOPMENT AND TECHNICAL ASSISTANCE AND RURAL EXTENSION FOR FAMILY FARMING - Araujo, Marcela Almeida de; Martins, Sergio Paganini; Sparovek, Gerd; Ranieri, Simone Beatriz Lima; Rocha Junior, Adauto Brasilino (REVISTA DE AGRICULTURA, 2020)
In the last decade, significant changes in the national scenario have altered the productive and social dynamics of Family Agriculture (FA) and public policies for this public, such as Technical Assistance and Rural Extension (TARE), can play an important role in its strengthening. This study carried out a territorial analysis of the dynamics of access to TARE by FA in the last decade, through multiple data sources. The results show that the structuring of a new and efficient national TARE system must rely on: (i) state action, but not with the claim that they are the only source of such services; (ii) expansion of the performance of municipalities, where the participation of city halls may contribute to TARE becoming a quality service; (iii) continuous and quality training for extension workers; iv) creation of innovative financing mechanisms; and (v) promoting the integration of research and extension.